The brothel system as a social network: an approach to the sexual exploitation of women from a feminist perspective and social network analysis (Bahía Blanca, 2003-2015) - Riganti, Ma. Valentina (AWARI, 2023)
This article reconstructs the sexual exploitation networks that acted in the brothel system of Bahía Blanca and identifies its main actors between 2003 and 2015 from a feminist perspective and using Social Network Analysis (SNA) as a methodology. In the phase that began with post-convertibility, Bahía Blanca, a town located in the southwest of Buenos Aires (Argentina), had a series of geographical, economic and social characteristics that gave it relevance in the national brothel system. In addition, there were local ordinances regulating cabarets and clubs that came into tension with national laws on the prevention of pimping and provided the possibility for sexual exploitation networks to act legally. In this scenario, the main actors moved constantly in the tension between what was legal and what was illegal. The use of diverse sources, ranging from court cases to journalistic articles, analyzed considering the ARS, allowed us to characterize the resulting network and compute the degree centrality and the betweenness centrality of each node. Thus, we were able to recognize the central actors and link their prominence with some attributes they had. Likewise, among the final considerations we point out that the actors, relationships and norms of the brothel system were intertwined with Bahian society and that its operating logic was crossed by the existence of power relations based on gender.